2017
DOI: 10.1093/hmg/ddx098
|View full text |Cite
|
Sign up to set email alerts
|

Mutations in XLF/NHEJ1/Cernunnos gene results in downregulation of telomerase genes expression and telomere shortening

Abstract: NHEJ1-patients develop severe progressive lymphocytopenia and premature aging of hematopoietic stem cells (HSCs) at a young age. Here we show a patient with a homozygous-NHEJ1 mutation identified by whole exome-sequencing that developed severe pancytopenia and bone marrow aplasia correlating with the presence of short telomeres. The mutation resulted in a truncated protein. In an attempt to identify the mechanism behind the short telomere phenotype found in the NHEJ1-patient we downregulated NHEJ1 expression i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
13
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(16 citation statements)
references
References 47 publications
2
13
0
1
Order By: Relevance
“…19 This diagnostic scenario may be even more complicated since other rare congenital disorders are characterized by the concomitant impairment of both marrow precursor growth and the immune system, 20 as in the case of deficiencies of GATA2 or ADA2 (DADA2) 21,22 or in chromosomal breakage syndromes (CBS). 23,24 The correct identification of the disorders potentially underlying MFs is an important diagnostic challenge because of the relevant treatment and follow-up implications. 25 However, there are no data available on the prevalence of such conditions, especially in pediatric patients.…”
mentioning
confidence: 99%
“…19 This diagnostic scenario may be even more complicated since other rare congenital disorders are characterized by the concomitant impairment of both marrow precursor growth and the immune system, 20 as in the case of deficiencies of GATA2 or ADA2 (DADA2) 21,22 or in chromosomal breakage syndromes (CBS). 23,24 The correct identification of the disorders potentially underlying MFs is an important diagnostic challenge because of the relevant treatment and follow-up implications. 25 However, there are no data available on the prevalence of such conditions, especially in pediatric patients.…”
mentioning
confidence: 99%
“…However, clinical presentation and immunological profile were extremely different. The first patient showed a senescent phenotype with decreased TRECs, RTE and naive T-cells counts suggesting that the sustained self-renewal of T-cell pool was impaired, while P2 presented only a slight reduction in T-cell counts as it has been reported in Cernunnos/XLF deficient patients reported up to date with normal TRECs/KRECs and IgG levels (22).…”
Section: Discussionmentioning
confidence: 80%
“…To functionally validate these findings, we tested whether these transcripts are novel gene expression targets regulated by PGC-1α. We also included telomeric repeat binding factor 2 (TERF2), a protein directly associated with age-related maintenance of telomeres 69, 70 . RNA immunoprecipitation assays in induced Sham, WT-res and ΔRS-res cells further showed that PGC-1α specifically binds XRCC5 , XRCC6 , NHEJ1 and TERF2 mRNAs via the RS domain ( Fig.…”
Section: Resultsmentioning
confidence: 99%
“…7c, Supplementary Table 1 tab 5). Interestingly, they are linked to age-related telomere maintenance [67][68][69] , premature ageing and alteration of telomerase gene expression 70 . To functionally validate these findings, we tested whether these transcripts are novel gene expression targets regulated by PGC-1α.…”
Section: ) It Was Also Represented As a Volcano Plotmentioning
confidence: 99%